1979
DOI: 10.1017/s0022172400026292
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of selenite F, Muller-Kauffmann tetrathionate and Rappaport's medium for the isolation of salmonellas from sewage-polluted natural water using a pre-enrichment technique

Abstract: SUMMARYThree enrichment broths, selenite F, Muller-Kauffmann tetrathionate and Rappaport, were examined for their efficiency in salmonella isolation. The three media, prepared from single ingredients in the laboratory, were compared with their commercial equivalents. Laboratory-prepared media were more efficient for isolating salmonellas from sewage-polluted natural water samples. A pre-enrichment stage using buffered peptone water was employed throughout the investigation. The size of inoculum from the pre-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

1980
1980
1994
1994

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 26 publications
2
21
1
Order By: Relevance
“…Although the timing of subculture from enrichment media has a role in salmonella isolation and multiple subculture may be an important part of technique in some circumstances (Harvey & Phillips, 1955;Grunnet, 1975;Harvey & Price, 1982), in this study we found that incubation of the RB 10 medium beyond 24 h yielded no further salmonella isolations. This is inconsistent with the findings of other workers (Vassiliadis et al 1978;Harvey et al 1979;. All of the other procedures used yielded further isolations on subculture at 48 h. This must be considered as a point in favour of the use of Rappaport's broth at 43°C, since early isolation markedly reduces the cost of examination of specimens.…”
Section: Resultscontrasting
confidence: 77%
See 2 more Smart Citations
“…Although the timing of subculture from enrichment media has a role in salmonella isolation and multiple subculture may be an important part of technique in some circumstances (Harvey & Phillips, 1955;Grunnet, 1975;Harvey & Price, 1982), in this study we found that incubation of the RB 10 medium beyond 24 h yielded no further salmonella isolations. This is inconsistent with the findings of other workers (Vassiliadis et al 1978;Harvey et al 1979;. All of the other procedures used yielded further isolations on subculture at 48 h. This must be considered as a point in favour of the use of Rappaport's broth at 43°C, since early isolation markedly reduces the cost of examination of specimens.…”
Section: Resultscontrasting
confidence: 77%
“…Tetrathionate broth was superior to selenite. Previous reports on the isolation of salmonellae from a number of sources, including pork sausages, minced meat, sewage, pig faeces (Vassiliadis et al 1977(Vassiliadis et al , 1978a, sewage-polluted water (Harvey et al 1979) and chicken giblets have all recommended the use of Rappaport's broth. In support of these findings this study has shown that when used to recover salmonellae from seagull cloacal swabs, Rappaport's broth is significantly superior to either selenite F or Muller-Kauffmann tetrathionate broth, both in terms of the number of salmonella isolates and in the variety of serotypes obtained.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 24 h subculture is more convenient than the 6 h for laboratory routine. The technique is simple and the 16 % gain (Table 1) compares favourably with the 2-6 % gain obtained in an earlier study by subculture from Rappaport's enrichment at 24 and 48 h (Harvey, Price & Xirouchaki, 1979). In contrast to selenite F and Muller-Kauffmann tetrathionate, 24 h appears to be near the optimum timing for subculture from Rappaport.…”
Section: Discussionsupporting
confidence: 62%
“…Whilst it has been suggested that commercially prepared products are often not as efficient as those produced from individual constituents (Harvey, Price & Xirouchaki, 1979) their convenience makes their use desirable. However, before any dehydrated product is used for routine work its efficiency should be compared with the same medium prepared from individual constituents.…”
Section: Discussionmentioning
confidence: 99%